1995
DOI: 10.1016/0014-5793(95)01285-3
|View full text |Cite
|
Sign up to set email alerts
|

cDNA sequences of three sheep myeloid cathelicidins

Abstract: Several myeloid antimicrobial peptide precursors have been shown to consist of a N-terminal proregion similar to a protein named cathelin and a structurally varied C-terminal antimicrobial domain. Proteins with these features have been named cathelicidins. In this paper we report the cDNA sequences of three ovine cathelicidins of 155, 160 and 190 residues, respectively, with cationic C-terminal sequences corresponding to putative antimicrobial domains. These are structurally varied and include a Cys-rich seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 40 publications
1
81
0
Order By: Relevance
“…This molecule is a new member of a large family of antimicrobial peptide precursors found in human (13,28), pig (6,8,14,29,30), cow (9, 31), rabbit (12), and sheep (10,11). The homology among the precursors of these antimicrobial peptides lies in a common NH 2 -terminal region of the unprocessed precursor known as cathelin and has led to use of the term cathelicidins to describe the gene family.…”
Section: Discussionmentioning
confidence: 99%
“…This molecule is a new member of a large family of antimicrobial peptide precursors found in human (13,28), pig (6,8,14,29,30), cow (9, 31), rabbit (12), and sheep (10,11). The homology among the precursors of these antimicrobial peptides lies in a common NH 2 -terminal region of the unprocessed precursor known as cathelin and has led to use of the term cathelicidins to describe the gene family.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the novel peptide of this work is proposed to be a new pleurocidin-like peptide. According to posttranslational modification principles, a putative proteolytic cleavage site existed, we suggested that the mature peptide containing 24 amino-acid residues with the glycine following arginine was processed to a C-terminal amide, [19][20][21] and designated HKPLP (Hi. K. Bleeker pleurocidin-like peptide).…”
Section: Sequence Analysismentioning
confidence: 99%
“…The structure and composition of SMAP29 (also known as SC5) was first deduced from sheep myeloid DNA [44,45] and later synthesized to assess its antimicrobial activity [11,43,46]. SMAP29 has broad-spectrum antimicrobial activity against Gramnegative and Gram-positive bacteria and fungi [11,43,45,46], is active in both low and high ionic strength conditions [11], and induces significant morphological alterations in bacterial surfaces [46,48].…”
Section: Cationic Antimicrobial Peptidesmentioning
confidence: 99%